Repotenciación de las etapas eléctrica y de control de una máquina inyectora de plástico para la empresa Juan Moreira - Pin Rivera, Diego Andrés (2023)
Innovation is the path by today’s companies around the world so they can increase their level of production and reduce the likelihood of failures that occurred in old machinery. Since a big percentage of micro entrepreneurs, due to their investment capacity, cannot afford to acquire the latest model, so they choose, instead, to optimize the components of the machines they already own, improving their quality and capacity of production, minimizing, as much as they can investment costs. With this approach in mind, the project is focused on repowering a Sandretto plastic injection machine, since its components to be replaced, continued with their dismantling, identification and change of electrical wiring. In addition, a new programmable logic controller (PLC) is incorporated, which manages all movements of the injection machine cyclically and has a fault identifier system in the form of an alarm. This modernization of the electrical and electronic panel is recorded in an operator’s manual, so the user can identify the integrated circuits in the machine, in addition, it has a code of faults and solutions, incase of requiring a corrective maintenance.